Neurofeedback in substance and non substance-related addictions: a mini review of current evidence and future directions - Sanader Vukadinovic, Bruna (Frontiers in Psychiatry, 2025)
Neurofeedback (NF) is emerging as a promising adjunctive intervention for substance use disorders (SUDs) and behavioral addictions. By providing real-time feedback on brain activity, NF enables individuals to self-regulate neural circuits implicated in craving, reward processing, and executive control. This mini review synthesizes recent evidence regarding the efficacy, mechanisms, and clinical applications of NF in addiction treatment. Addiction remains a major public health concern characterized by high relapse rates and limited long-term success from pharmacological and psychosocial therapies, underscoring the need for innovative approaches. Studies included in this review were identified through PubMed, Scopus, and Web of Science using the terms “neurofeedback,” “EEG,” “fMRI,” “addiction,” “substance use disorder,” “behavioral addiction,” and “craving,” with priority given to publications from 2019–2025. Two primary NF modalities have been examined: electroencephalography (EEG)-based and functional magnetic resonance imaging (fMRI)-based neurofeedback. EEG-NF, particularly the alpha–theta protocol, has demonstrated reductions in craving, anxiety, and relapse rates among individuals with alcohol and substance dependence. fMRI-NF enables targeted modulation of addiction-related brain regions, such as the insula and dorsolateral prefrontal cortex, with region-specific but variable clinical effects. Systematic reviews indicate that NF, especially EEG-based, reliably reduces craving and improves psychological outcomes, though methodological heterogeneity limits generalizability. Recent advances integrating NF with biofeedback and machine learning approaches suggest potential for personalized and multimodal interventions. Overall, NF represents a promising, neuroscience-informed adjunct in addiction treatment, warranting large-scale controlled trials to establish efficacy and optimize clinical application.